O5-S4.02 Successful interventions to increase use of patient self obtained vaginal swabs for chlamydia/gonorrhoea testing in WA State. (10th July 2011) - Goldenkranz, S; Fine, D; Knutson, C; Loza, R
Abstract : Background: Patient Self-Obtained Vaginal Swabs (SOVs) are the most sensitive and specific technology for chlamydia (CT) and gonorrhoea (GC) testing. While SOVs enhance clinic efficiency and client access to testing, uptake of this innovation has been slow. The 10 USPHS Regional Infertility Prevention Projects (IPP) collect CT/GC test data from Family Planning, STD, and other publicly-funded clinics across the U.S. By 2010, only two regional IPPs reported using vaginal swabs. Washington (WA) State has been a leader in SOV promotion and collects common supplemental data to evaluate uptake. Objectives: (1) Describe WA SOV interventions; (2) Describe clinics' adoption and use of SOVs; (3) Explore trends and associations in SOV use vs other specimen sources. Methods: In 2011, key stakeholders were interviewed about SOV interventions. WA IPP data from female patients were compiled from 1/2007 to 6/2010. Clinic and client factors associated with SOVs were explored including visit date, clinic type, client demographics, specimen source, and test results. Multivariate models were developed. An aggregate clinic-level dataset was generated to assess SOV uptake in clinics averaging >25 tests/year. Significant (p<0.05) results are reported. Results: In 2008, WA Department of Health declared SOV promotion a state-wide objective. Interventions included development and dissemination of patient instructions, provider education materials and webinars; direct communication and follow-up with clinic management; and data monitoring. Of 126 IPP clinics, % using SOVs increased significantly from 9.3% in 2007 to 76.8% in 2010. Among clinics using SOVs, mean % of CT/GC specimen obtained by SOVs increased from 1.7% to 27.2%. During the study period, 176, 234 total CT/GC specimen were obtained. SOV use rose 16.6% overall (from 0.3% in 2007 to 16.9% in 2010), replacing 12.2% of clinician-obtained and 4.4% of urine-based specimen (Abstract O5-S4.02 table 1 ). Factors independently associated with SOV use were: client age <20 (AOR=1.55) and clinic type (FP: ref., STD: AOR=0.27, School-Based: AOR=5.44, Women's Health: AOR=0.07). Client race, ethnicity, and CT/GC positivity were not associated. Conclusions: Since 2007, SOV use increased substantially across WA state and within individual clinics. SOVs are replacing clinician-obtained and urine specimens. More work is needed to improve uptake across the variety of clinic types. WA's successful intervention and evaluation activities can be a model for other states.